Invisibility of class identity in Turkish media: news coverage of class identity and class-based policies - Sen, Ayse Fulya (Palgrave Macmillan Ltd, 2017)
One of the primary requirements of a democratic media is to represent the interests of different social groups in the society it seeks to serve. Since the dominant class invariably has control over the media industry, media outputs typically reflects its own viewpoints or perspectives. Using a content analysis method this study discusses the invisibility and under-representation of class identity and examines news coverage of the automotive and glassware workers' strikes and the class-based issues in Turkey. We attempt to reveal the under-representation of class identity and how the media constructs a dominant ideology in capitalist societies, including how class identity is excluded from the mainstream media in the case of Turkey. Our findings reveal that class identity has been under-represented in the news media.